2017
DOI: 10.1002/app.45289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface modification of silicon carbide nanoparticles on the properties of nanocomposites based on epoxidized natural rubber/natural rubber blends

Abstract: Improvement of the properties of rubber nanocomposites is a challenge for the rubber industry because of the need for higher performance materials. Addition of a nanometer‐sized filler such as silicon carbide (SiC) to enhance the mechanical properties of rubber nanocomposites has rarely been attempted. The main problem associated with using SiC nanoparticles as a reinforcing natural rubber (NR) filler compound is poor dispersion of SiC in the NR matrix because of their incompatibility. To solve this problem, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…The tan δ max represents the height of the peak of the relation between tan δ and temperature. The value of tan δ max is inversely proportional to the interfacial adhesion between the polymer matrix and filler; as the interfacial adhesion increases the value of tan δ max decreases 49 . As can be shown from Table 3, the composites which contain CF displayed a lower tan δ max than the corresponding UF filled composites, which indicates that the coating of SF by SBA improves the interfacial adhesion between NR and SF.…”
Section: Resultsmentioning
confidence: 86%
“…The tan δ max represents the height of the peak of the relation between tan δ and temperature. The value of tan δ max is inversely proportional to the interfacial adhesion between the polymer matrix and filler; as the interfacial adhesion increases the value of tan δ max decreases 49 . As can be shown from Table 3, the composites which contain CF displayed a lower tan δ max than the corresponding UF filled composites, which indicates that the coating of SF by SBA improves the interfacial adhesion between NR and SF.…”
Section: Resultsmentioning
confidence: 86%
“…The blending of rubbers has become an increasingly important area of research activity to get the optimum properties of the rubber product for a specified span in a particular environment. For industrial applications, a large number of rubber‐rubber blends have been reported but most of them do not have the required mechanical properties due to their incompatibility and viscosity mismatch problems 1,2 . Incompatibility between the blend components does not blend properly to produce a uniform or homogeneous mixture and this leads to poor mechanical properties of the resultant polymer blend as compared to the individual rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13–15 ] SiC particles are also increasingly used in composite materials for example, to tune the mechanical properties of rubber. [ 186 ] Despite SiC NPs’ versatile and tunable fluorescence from the UV to NIR spectral ranges, applications that employ these properties are only slowly emerging. Compared to the wide use of fluorescent color centers in diamond NPs for imaging and sensing applications, applications of SiC NPs in these areas are still in their infancy and hence present a great potential for new discoveries and innovation.…”
Section: Applicationsmentioning
confidence: 99%